Phase angle of bioelectrical impedance analysis as an indicator for diabetic polyneuropathy in type 2 Diabetes Mellitus - Schimpfle, Lukas; Tsilingiris, Dimitrios; Mooshage, Christoph; Kender, Zoltán; Sulaj, Alba; Rauchhaupt, Ekaterina von; Szendrödi, Julia; Herzig, Stephan; Goepfert, Jens; Groener, Jan; Nawroth, Peter Paul; Bendszus, Martin; et al. (The journal of clinical endocrinology & metabolism, 2024)
Due to the heterogenous clinical symptoms and deficits, the diagnosis of diabetic polyneuropathy (DPN) is still difficult in clinical routines, leading to increased morbidity and mortality.We studied the correlation of phase angle (PhA) of bioelectrical impedance analysis (BIA) with clinical, laboratory, and physical markers of DPN to evaluate PhA as a possible diagnostic method for DPN.In this cross-sectional observational study as part of the Heidelberg Study on Diabetes and Complications, we examined 104 healthy individuals and 205 patients with type 2 diabetes mellitus (T2D), among which 63 had DPN. The PhA was calculated from multifrequency BIA. Nerve conduction studies, quantitative sensory testing (QST) and diffusion-weighted magnetic resonance neurography to determine fractional anisotropy (FA) reflecting peripheral nerve integrity were performed.T2D patients with DPN had lower PhA values (5.71 ± 0.10) compared to T2D patients without DPN (6.07 ± 0.08, P = .007, + 6.1%) and healthy controls (6.18 ± 0.08, P < .001, + 7.9%). Confounder-adjusted analyses showed correlations of the PhA with conduction velocities and amplitudes of the peroneal (β=.28; β=.31, P < .001) and tibial nerves (β=.28; β=.32, P < .001), Z-scores of QST (thermal detection β=.30, P < .05) and the FA (β=.60, P < .001). Receiver-operating characteristic analysis showed similar performance of PhA in comparison to the mentioned diagnostic methods.The study shows that PhA is, in comparison to other test systems used, at least an equally good and much easier to handle investigator-independent marker for detection of DPN.